Indoor WIFI Signal Prediction Using Modelized Heatmap Generator Tool - Wanchai Sangkusolwong (2018)
© 2017 IEEE. Wireless design is essential as it provides time and cost saving. Several WIFI planning tools are available on the market but most of them were initially designed to be user-friendly and provided limited configuration options making it hard to model site-specific environment factors. In this paper, we proposed a WIFI heatmap generator tool that allows users to predict wireless signal strength within the building. Our tool allows users to characterize wireless propagation model including pathloss exponent and pathloss attenuation factors which are usually caused by wall partitions, building layouts, etc. Network administrators and wireless users can deploy this tool to visualize heatmaps which represent wireless received signal strength in each location of the floor plan. Limited WIFI coverage area can be easily determined using this tool. This can be helpful during access point deployment and redeployment. A site-specific propagation model was proposed, and the accuracy of this model was discussed at the end of this paper.